Electrophoretic purification of recombinant green fluorescent protein from intact escherichia coli cells in continuous buffer system - Chau, King Hou (2014)
Green fluorescent protein (GFP) is a protein that consists of 27 kDa protein of 238 amino acid residues. GFP emits bright green fluorescence light when exposed to blue or ultraviolet light. GFP has been used as a marker for the gene expression visualization, protein localization in living and fixed tissues as well as for protein targeting in intact cells and organisms. A direct purification method was developed to purify the recombinant GFP from intact Escherichia coli (E. coli) cells using preparative native polyacrylamide gel electrophoresis (n-PAGE) in continuous buffer system. 100 μL of 12% (w/v) polyacrylamide gel was used to study the effect of biomass concentration and the effect of resolving gel height on the preparative n-PAGE. The amount of purified GFP was determined by using the gel-based imaging method and the Lowry protein determination method to determine the purity and yield of the recovered GFP. The optimal biomass concentration in the feedstock was found at 15% (w/v) with 62.5% of purity. The purity of GFP slightly reduced when the biomass concentration increased to 25% (w/v). Meanwhile, 89% of purity was achieved when 1 cm of resolving gel was employed in preparative n-PAGE. The purity of the GFP decreased when the gel height increased to 2.5cm. However, the percentage of the yield in this study was unable to determine since the calculation was completely offset